Antioxidant potential of polar and non polar solvent extracts of Aphanamyxis polystachya in vitro - Chaitra Narayan; Ravishankar Vittal Rai (International Journal of Phytomedicine, 2014)
Aphanamixis polystachya (Wall.) Parker, vernacularly called “Amoora rohituka” is a medicinal plant belonging to the family of Meliaceae and appearing among Indian natural drugs used as remedy as an astringent and applied on swelling after a fall. In recent times anti carcinogenic ingredients are found from this plant. The search for safe therapeutic molecules suitable for long term use are most needed today to prevent the progression of free radical mediated diseases. Hence, the antioxidant activity of polar and non-polar solvent extracts of the leaf of Aphanamixis polystachya was evaluated in a series of in vitro assay involving free radicals and reactive oxygen species. The extract exhibited its scavenging effect in concentration dependent manner depending on the solvent extract on superoxide anion radicals, DPPH radical scavenging and property of metal chelating and reducing power. The extract has shown considerably good value for total reducing power, total phenolics, flavanoids and flavanol content.